Definition of infection after fracture fixation: A systematic review of randomized controlled trials to evaluate current practice. Issue 3 (March 2018) - Metsemakers, WJ.; Kortram, K.; Morgenstern, M.; Moriarty, T.F.; Meex, I.; Kuehl, R.; Nijs, S.; Richards, R.G.; Raschke, M.; Borens, O.; Kates, SL.; Zalavras, C.; et al.
Abstract: Introduction: One of the most challenging musculoskeletal complications in modern trauma surgery is infection after fracture fixation (IAFF). Although infections are clinically obvious in many cases, a clear definition of the term IAFF is crucial, not only for the evaluation of published research data but also for the establishment of uniform treatment concepts. The aim of this systematic review was to identify the definitions used in the scientific literature to describe infectious complications after internal fixation of fractures. The hypothesis of this study was that the majority of fracture-related literature do not define IAFF. Material and methods: A comprehensive search was performed in Embase, Cochrane, Google Scholar, Medline (OvidSP), PubMed publisher and Web-of-Science for randomized controlled trials (RCTs) on fracture fixation. Data were collected on the definition of infectious complications after fracture fixation used in each study. Study selection was accomplished through two phases. During the first phase, titles and abstracts were reviewed for relevance, and the full texts of relevant articles were obtained. During the second phase, full-text articles were reviewed. All definitions were literally extracted and collected in a database. Then, a classification was designed to rate the quality of the description of IAFF. Results: A total of 100 RCT's were identified in the search. Of 100 studies, only two (2%) cited a validated definition to describe IAFF. In 28 (28%) RCTs, the authors used a self-designed definition. In the other 70 RCTs, (70%) there was no description of a definition in the Methods section, although all of the articles described infections as an outcome parameter in the Results section. Conclusion: This systematic review shows that IAFF is not defined in a large majority of the fracture-related literature. To our knowledge, this is the first study conducted with the objective to explore this important issue. The lack of a consensus definition remains a problem in current orthopedic trauma research and treatment and this void should be addressed in the near future.